Ancestral Sequence Reconstructions of MotB Are Proton-Motile and Require MotA for Motility - Islam, Md Imtiazul; Lin, Angela; Lai, Yu-Wen; Matzke, Nicholas J.; Baker, Matthew A. B. (Frontiers in Microbiology, 2020)
The bacterial flagellar motor (BFM) is a nanomachine that rotates the flagellum to propel many known bacteria. The BFM is powered by ion transit across the cell membrane through the stator complex, a membrane protein. Different bacteria use various ions to run their BFM, but the majority of BFMs are powered by either proton (H+) or sodium (Na+) ions. The transmembrane (TM) domain of the B-subunit of the stator complex is crucial for ion selectivity, as it forms the ion channel in complex with TM3 and TM4 of the A-subunit. In this study, we reconstructed and engineered thirteen ancestral sequences of the stator B-subunit to evaluate the functional properties and ionic power source of the stator proteins at reconstruction nodes to evaluate the potential of ancestral sequence reconstruction (ASR) methods for stator engineering and to test specific motifs previously hypothesized to be involved in ion-selectivity. We found that all thirteen of our reconstructed ancient B-subunit proteins could assemble into functional stator complexes in combination with the contemporary Escherichia coli MotA-subunit to restore motility in stator deleted E. coli strains. The flagellar rotation of the thirteen ancestral MotBs was found to be Na+ independent which suggested that the F30/Y30 residue was not significantly correlated with sodium/proton phenotype, in contrast to what we had reported previously. Additionally, four among the thirteen reconstructed B-subunits were compatible with the A-subunit of Aquifex aeolicus and able to function in a sodium-independent manner. Overall, this work demonstrates the use of ancestral reconstruction to generate novel stators and quantify which residues are correlated with which ionic power source.